On Matching Revenue With Expense. - Hylton, Delmer P. (The Accounting Review, 1965)
Abstract The article suggests that matching revenue and expense should be defined as assigning revenue earned and expense incurred to the accounting period in which these events occur. The absence of revenue should not be used as justification for capitalizing expenses. Fixed relationships between revenue and expense should not be assumed. Where such a relationship is established by contract, such as on cost-plus contracts, it is acceptable to measure revenue in relation to cost incurred. Cost should be written off over the periods of expected contribution to revenue. It is futile and unnecessary to try to apportion these costs in relation to assumed amounts of periodic revenue. The decision to capitalize expenditures for amortization in future periods should be based on the probability that such costs will produce additional revenue in those periods. Thus, the use of the accrual basis does not and should not include an estimate of the amount of future revenue to be received. In the unusual case where both revenue and expense can be accurately predicted, then and only then should a fixed relationship be used.